Carbon ceramic resistor and preparation method and application thereof

By using composite conductive particles with multi-stage pores in carbon ceramic resistors, the problem of uneven distribution of conductive carbon is solved, the conductive performance and stability of the resistor are improved, and current breakdown is avoided.

CN119480306APending Publication Date: 2025-02-18GUANGDONG POWER GRID CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411608315.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The content and distribution of conductive carbon components in carbon ceramic resistors are difficult to control, resulting in unstable resistivity and current breakdown problems.

Method used

By constructing multi-stage pore composite conductive particles, including conductive carbon and alumina, and evenly dispersing these particles in the ceramic matrix, avoiding agglomeration of conductive fillers and improving conductive properties and stability.

Benefits of technology

The uniform distribution of carbon materials in carbon ceramic resistors is achieved, the overall conductivity, strength and stability of the resistor are improved, and the current breakdown problem is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480306A_ABST
    Figure CN119480306A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of production of special materials for electrical equipment, and provides a carbon ceramic resistor and a preparation method and application thereof in view of problems existing in the prior art. Composite conductive particles are uniformly dispersed in a ceramic matrix of the carbon ceramic resistor; the composite conductive particles comprise conductive carbon and aluminum oxide and are provided with hierarchical pores; the conductive carbon is constructed in the hierarchical porous composite conductive particles, and the dispersion of the carbon material is adjusted into the dispersion and distribution of the composite conductive particles in the ceramic matrix, so that the carbon material is more uniformly distributed in the carbon ceramic resistor; the phenomenon that conductive filler is prone to agglomeration due to the fact that a conductive carbon material is directly mixed with a ceramic material in a traditional method is avoided, meanwhile, due to the existence of aluminum oxide, interface bonding of the composite conductive particles and the ceramic matrix is tighter, and the overall conductive performance, strength and stability of the carbon ceramic resistor can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of special material production for electrical equipment, and relates to a carbon ceramic resistor and a preparation method and application thereof. Background Art

[0002] With the rapid expansion of power infrastructure and the booming power industry, resistor materials in high-voltage switchgear are facing increasing performance requirements. In ultra-high voltage power transmission networks, ceramic resistors are the core safety and protection mechanism, and their excellent stability and safety have become an important yardstick for measuring the overall operation quality of the power grid. This key component plays an indispensable role in ultra-high voltage and UHV transmission equipment, which is directly related to the continuity of power transmission and the overall safety of the power grid system.

[0003] Carbon ceramic resistors are a type of closing resistor used as high-voltage circuit breakers. They limit overvoltage and weaken electromagnetic oscillations, and are one of the core electrical protection components for the development of ultra-high voltage and UHV power transmission and transformation equipment. Carbon ceramic resistors are used in series in switches and need to withstand impulse voltages and absorb oscillation wave energy. They require high precision in resistance values ​​and resistor dimensions to prevent damage caused by uneven load on the resistor sheet. At the same time, carbon ceramic resistors often need to be porous ceramics to meet the requirements for ceramics to withstand thermal shock.

[0004] In actual production and application, the content and distribution control of the conductive carbon component in carbon ceramic resistors have a significant impact on meeting the above performance requirements. Specifically, if the amount of carbon material added is too low, the resistivity requirements cannot be met, and if the amount added is too high, its sintering behavior will be affected, thereby reducing its mechanical properties. This uneven distribution problem will cause certain areas of the resistor to absorb energy and release heat. As a result, these areas of concentrated energy absorption may be overloaded due to the strong effect of the current, eventually leading to current breakdown of the resistor. Therefore, during the design and manufacturing process, special attention should be paid to the uniform distribution of carbon materials to avoid the problem of resistor breakdown caused by agglomeration and segregation.

[0005] The preparation process of carbon ceramic resistors has a great influence on their performance and precision. Studying the influence of preparation process parameters on resistor performance is an important condition for obtaining high-reliability resistors. Therefore, developing new uniformly distributed carbon ceramic resistors and their preparation process methods so that carbon materials can achieve better dispersion effects is of great significance for improving the performance and reliability of carbon ceramic resistors and ensuring the reliable operation of power systems. Summary of the invention

[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a carbon ceramic resistor and a preparation method and use thereof, wherein composite conductive particles are uniformly dispersed in a ceramic matrix of the carbon ceramic resistor, and the components of the composite conductive particles include conductive carbon and aluminum oxide and have multi-level pores; the present invention constructs conductive carbon in composite conductive particles with multi-level pores, and adjusts the dispersion of carbon materials to the dispersion and distribution of composite conductive particles in the ceramic matrix. In this way, the carbon material is more evenly distributed in the carbon ceramic resistor, avoiding the phenomenon of easy agglomeration of conductive fillers caused by the traditional method of directly mixing conductive carbon materials with ceramic materials. At the same time, due to the presence of aluminum oxide, the interface between the composite conductive particles and the ceramic matrix is ​​more tightly bonded, which helps to improve the overall conductivity, strength and stability of the carbon ceramic resistor.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a carbon ceramic resistor, comprising a ceramic matrix in which composite conductive particles are dispersed, wherein the composite conductive particles include conductive carbon and aluminum oxide; and the composite conductive particles have multi-level pores.

[0009] The present invention constructs conductive carbon in composite conductive particles with multi-level pores, and adjusts the dispersion of conventional carbon materials as conductive fillers to the dispersion and distribution of composite conductive particles as conductive fillers in a ceramic matrix. This method makes the carbon material more evenly distributed in the carbon ceramic resistor, avoiding the phenomenon of conductive filler agglomeration caused by the traditional method of directly mixing conductive carbon materials with ceramic materials. At the same time, due to the presence of aluminum oxide, the interface between the composite conductive particles and the ceramic matrix is ​​more tightly bonded, which helps to improve the overall conductivity, strength and stability of the carbon ceramic resistor. The composite conductive particles have a multi-level pore structure that provides more attachment points and dispersion space for the conductive carbon, so that the conductive carbon can be more evenly distributed in the composite conductive particles.

[0010] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0011] As a preferred technical solution of the present invention, the composite conductive particles are spherical.

[0012] Preferably, the particle size of the composite conductive particles is 80-120 μm, for example, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm or 120 μm.

[0013] Preferably, the multi-level pores include nanopores and micropores.

[0014] Preferably, based on the mass of the composite conductive particles as 100%, the conductive carbon accounts for 2% to 7%, for example, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.2%, 3.4%, 3.7%, 4%, 4.2%, 4.5%, 4.8%, 5%, 5.3%, 5.6%, 5.8%, 6%, 6.2%, 6.5%, 6.8% or 7%, and the aluminum oxide accounts for 93% to 98%, for example, 9 3%, 93.3%, 93.5%, 93.8%, 94%, 94.3%, 94.5%, 94.8%, 95%, 95.3%, 95.5%, 95.8%, 96%, 96.2%, 96.5%, 96.8%, 97%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97.8%, 97.9% or 98%, etc.

[0015] Preferably, based on the mass of the carbon ceramic resistor being 100%, the composite conductive particles account for 9% to 15%, for example, 9%, 9.3%, 9.5%, 9.8%, 10%, 10.2%, 10.5%, 10.8%, 11%, 11.3%, 11.5%, 11.8%, 12%, 12.2%, 12.4%, 12.6%, 12.8%, 13%, 13.3%, 13.5%, 13.8%, 14%, 14.2%, 14.5%, 15.9%, 16.1%, 16.2%, 16.3%, 16.4%, 16.6%, 16.8%, 17. 4.8% or 15%, etc., the ceramic matrix accounts for 85% to 91%, for example, 85%, 85.3%, 85.5%, 85.8%, 86%, 86.3%, 86.5%, 86.8%, 87%, 87.2%, 87.4%, 87.6%, 87.8%, 88%, 88.3%, 88.5%, 88.7%, 89%, 89.3%, 89.5%, 89.8%, 90%, 90.3%, 90.5%, 90.8% or 91%, etc.

[0016] In a second aspect, the present invention provides a method for preparing the carbon ceramic resistor according to the first aspect, comprising:

[0017] The composite conductive particles are mixed with a ceramic matrix raw material, and a first granulation is performed so that the ceramic matrix raw material covers the composite conductive particles to form a core-shell structure material; the core-shell structure material is molded to obtain a green body; and the green body is first sintered to obtain a carbon ceramic resistor.

[0018] The traditional method of preparing carbon ceramic resistors mainly relies on mixing carbon materials and ceramic powders evenly, shaping them through mechanical molding technology, and then sintering them under normal pressure. However, this method faces the problem that the conductive carbon component is difficult to disperse evenly in the ceramic matrix during the preparation process, which directly leads to the instability and difficulty in controlling the resistivity. The preparation method of the present invention combines composite conductive particles with ceramic matrix raw materials to form a precursor material with a core-shell structure. Sintering with this core-shell structure can avoid the problem of easy agglomeration of conductive fillers in traditional methods, effectively improve the uniformity of the dispersion and distribution of conductive carbon, and due to the presence of the outer layer material, the interface between the composite conductive particles and the ceramic matrix is ​​more tightly bonded, which is conducive to improving stability and facilitating the overall mechanical strength of the enhanced material after sintering.

[0019] As a preferred technical solution of the present invention, based on the total mass of the ceramic matrix raw material as 100%, the ceramic matrix raw material includes 48% to 50% of bauxite, such as 48%, 48.3%, 48.5%, 48.8%, 49%, 49.3%, 49.5%, 49.8% or 50%, etc.; 18% to 20% of potassium feldspar, such as 18%, 18.3%, 18.5%, 18.8%, 19%, 1 9.3%, 19.5%, 19.8% or 20%; 10% to 12% kaolin, for example 10%, 10.3%, 10.5%, 10.8%, 11%, 11.2%, 11.5%, 11.8% or 12%; and 20% to 22% clay, for example 20%, 20.3%, 20.5%, 20.8%, 21%, 21.2%, 21.5%, 21.8% or 22% etc.

[0020] As a preferred technical solution of the present invention, the first granulation method includes impregnation granulation; the impregnation granulation includes preparing the ceramic matrix raw material into a first slurry, and impregnating the composite conductive particles in the first slurry, so that the ceramic matrix raw material covers the composite conductive particles to form the core-shell structure material.

[0021] Preferably, the first slurry is pre-milled for 4 to 8 hours, for example, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours.

[0022] Preferably, the immersion time is 5 to 10 minutes, for example, 5 minutes, 5.5 minutes, 6 minutes, 6.5 minutes, 7 minutes, 7.5 minutes, 8 minutes, 8.5 minutes, 9 minutes, 9.5 minutes or 10 minutes.

[0023] Preferably, after the impregnation, the mixture is dried at 70-90°C, such as 70°C, 73°C, 75°C, 80°C, 83°C, 85°C, 88°C or 90°C for 1-3h, such as 1h, 1.3h, 1.5h, 1.8h, 2h, 2.3h, 2.5h, 2.8h or 3h.

[0024] Preferably, the dipping and drying process is repeated at least twice until the thickness of the shell layer reaches 40 to 60 μm, for example, 40 μm, 42 μm, 45 μm, 48 μm, 50 μm, 53 μm, 55 μm, 58 μm or 60 μm.

[0025] Preferably, the dipping is repeated 2 to 3 times, and the dipping, taking out and drying are performed once, and then the next dipping process is performed.

[0026] The present invention preferably controls the coating thickness of the shell layer (ceramic matrix raw material) by controlling the immersion time and the number of immersion repetitions, and controls it within the preferred thickness, which not only ensures a good combination between the conductive filler and the ceramic matrix, but also avoids the problem of increased resistivity or decreased conductivity caused by an excessively thick shell layer.

[0027] Preferably, the ceramic matrix raw material and water are prepared into the first slurry according to a solid-liquid mass ratio of 1:(0.5-2), for example, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8 or 1:2.

[0028] As a preferred technical solution of the present invention, the molding includes first pre-molding at 90 to 110 MPa, for example, 90 MPa, 92 MPa, 95 MPa, 98 MPa, 100 MPa, 103 MPa, 105 MPa, 108 MPa or 110 MPa, and then increasing the molding pressure to 95 to 115 MPa for isostatic pressing, for example, 95 MPa, 98 MPa, 100 MPa, 102 MPa, 105 MPa, 108 MPa, 110 MPa, 113 MPa or 115 MPa.

[0029] Preferably, the first sintering method comprises oscillating pressure sintering assisted flash sintering.

[0030] Preferably, the process of oscillating pressure sintering assisted flash firing comprises: preheating the green body to 550-650°C, such as 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C, and keeping it warm for 1-3h, such as 1h, 1.3h, 1.5h, 1.8h, 2h, 2.3h, 2.5h, 2.8h or 3h, to ensure temperature uniformity; then, starting to apply pressure and simultaneously raising the temperature to 900-1100°C, such as 900°C, 930°C, 950°C, 980°C , 1000℃, 1030℃, 1050℃, 1080℃ or 1100℃, etc., and then keep warm for 0.5-1h, such as 0.5h, 0.6h, 0.7h, 0.8h, 0.9h or 1h, etc., to promote the densification and grain growth of the material; finally, when the temperature reaches the flash trigger temperature of 1200-1400℃, such as 1200℃, 1230℃, 1250℃, 1280℃, 1300℃, 1330℃, 1350℃, 1380℃ or 1400℃, etc., set opposite electrode sheets on the opposite side surfaces of the green body, and apply 8-12mA / mm 2 Current density, for example 8mA / mm 2 、8.5mA / mm 2 , 9mA / mm 2 , 9.5mA / mm 2 , 10mA / mm 2 , 10.5mA / mm 2 , 11mA / mm 2 , 11.5mA / mm 2 or 12mA / mm 2 etc., and an electric field strength of 6000-7000V / cm, such as 6000V / cm, 6100V / cm, 6200V / cm, 6300V / cm, 6400V / cm, 6500V / cm, 6600V / cm, 6700V / cm, 6800V / cm, 6900V / cm or 7000V / cm, etc., while controlling the constant current time to be less than 1s for flash burning, such as 0.1s, 0.2s, 0.3s, 0.4s, 0.5s, 0.6s, 0.7s, 0.8s or 0.9s, etc.

[0031] The present invention preferably adopts oscillating pressure sintering assisted flash firing technology. Compared with the traditional sintering method, this process can reach a higher sintering temperature in a shorter time while maintaining the uniformity and density of the sample.

[0032] As a preferred technical solution of the present invention, the method for preparing the composite conductive particles comprises:

[0033] A carbon precursor and an aluminum oxide precursor are mixed in a liquid phase system to obtain a second slurry; the second slurry is subjected to a second granulation to obtain a composite precursor; and the composite precursor is subjected to a second sintering to obtain composite conductive particles with multi-level pores.

[0034] As a preferred technical solution of the present invention, the carbon precursor includes citric acid monohydrate.

[0035] Preferably, the aluminum oxide precursor comprises aluminum sol.

[0036] Preferably, the mass concentration of the aluminum sol is 10% to 40%, for example, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38% or 40%, etc.

[0037] Preferably, based on the total mass of the carbon precursor and the aluminum oxide precursor as 100, the carbon precursor accounts for 20% to 30%, for example, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%.

[0038] Preferably, the second granulation method comprises spray granulation.

[0039] Preferably, the viscosity of the second slurry is 1000-2000 cP, for example, 1000 cP, 1100 cP, 1200 cP, 1300 cP, 1400 cP, 1500 cP, 1600 cP, 1700 cP, 1800 cP, 1900 cP or 2000 cP.

[0040] Preferably, the second sintering temperature is 900-1100°C, for example, 900°C, 930°C, 950°C, 980°C, 1000°C, 1030°C, 1050°C, 1080°C or 1100°C.

[0041] In a third aspect, the present invention provides a closing resistor, which contains the carbon ceramic resistor described in the first aspect, or contains the carbon ceramic resistor obtained by the preparation method described in the second aspect.

[0042] In a fourth aspect, the present invention provides a method for manufacturing the closing resistor described in the third aspect, the manufacturing method comprising sequentially subjecting the carbon ceramic resistor to mechanical grinding and electrode coating to obtain a closing resistor.

[0043] It should be noted that due to space limitations and to avoid redundancy, the present invention does not list all point values ​​within the above numerical range one by one, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0044] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0045] The present invention constructs conductive carbon into composite conductive particles with multi-level pores and utilizes the dispersion of the composite conductive particles in a ceramic matrix to achieve uniform dispersion and distribution of the conductive carbon, thereby avoiding the phenomenon of conductive filler agglomeration caused by the traditional method of directly mixing conductive carbon materials with ceramic materials. At the same time, due to the presence of aluminum oxide, the interface between the composite conductive particles and the ceramic matrix is ​​more tightly bonded, which helps to improve the overall conductivity, strength and stability of the carbon ceramic resistor.

[0046] The preparation method of the carbon ceramic resistor described in the present invention combines composite conductive particles with ceramic matrix raw materials to form a precursor material with a core-shell structure. Sintering with this core-shell structure can avoid the problem of easy agglomeration of conductive fillers in traditional methods, effectively improve the uniformity of the dispersion and distribution of conductive carbon, and due to the presence of the outer layer material, the interface between the composite conductive particles and the ceramic matrix is ​​more tightly bonded, which is beneficial to improving stability and facilitating the overall mechanical strength of the enhanced material after sintering.

[0047] The preparation method of the carbon ceramic resistor described in the present invention controls the coating thickness of the shell layer (ceramic matrix raw material) by controlling the immersion time and the number of immersions, and controls it within the preferred thickness, thereby further ensuring a good combination between the conductive filler and the ceramic matrix, and avoiding the problem of increased resistivity or decreased conductivity due to an excessively thick shell layer.

[0048] The preparation method of the carbon ceramic resistor described in the present invention adopts oscillating pressure sintering assisted flash firing technology. Compared with the traditional sintering method, this process can reach a higher sintering temperature in a shorter time while maintaining the uniformity and density of the sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a schematic diagram of the various components and their structural relationships in the carbon ceramic resistor in Example 1.

[0050] Figure 1 Middle: 1-ceramic matrix, 2-composite conductive particles, 3-nanopores, 4-micropores. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0052] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0053] Example 1

[0054] This embodiment provides a carbon ceramic resistor, such as Figure 1As shown, it includes a ceramic matrix 1, in which spherical composite conductive particles 2 are dispersed, and the components of the composite conductive particles 2 include conductive carbon and aluminum oxide; the composite conductive particles 2 have multi-level pores; the particle size of the composite conductive particles 2 is 100μm, and the multi-level pores include nanopores 3 and micropores 4. If the mass of the composite conductive particles 2 is 100%, the conductive carbon accounts for 4%, and the aluminum oxide accounts for 96%. If the mass of the carbon ceramic resistor is 100%, the composite conductive particles 2 account for 12%, and the ceramic matrix 1 accounts for 88%.

[0055] The preparation method of the carbon ceramic resistor comprises:

[0056] (1) Preparation of composite conductive particles:

[0057] The carbon precursor citric acid monohydrate and the aluminum precursor aluminum sol (the mass concentration of the aluminum sol is 25%) are mixed together in a mass ratio of 25:75, and stirred evenly in a stirrer for 30 minutes to ensure that the two precursors are fully mixed without agglomeration. An appropriate amount of deionized water is added to adjust the viscosity to 1500 cP to obtain a second slurry;

[0058] The obtained second slurry was spray granulated using a spray granulator, the air inlet temperature was set to 240° C., the air outlet temperature was set to 100° C., the dried spherical particles were collected and sieved, and the spherical particles under the 20-mesh diameter sieve were selected;

[0059] The screened spherical particles are placed in a high-temperature sintering furnace, heated to 1000°C at a heating rate of 5°C / min, kept at this temperature for 2 hours to complete the second sintering, and taken out after naturally cooling to room temperature to obtain composite conductive particles;

[0060] (2) Preparation of core-shell structure materials:

[0061] Providing a ceramic matrix raw material, calculating the total mass as 100%, mixing 49% of bauxite, 19% of potassium feldspar, 11% of kaolin, 21% of clay and 0.3% of water glass in proportion, adding deionized water at a solid-liquid mass ratio of 1:0.5, and ball milling in a ball mill for 6 hours to obtain a first slurry;

[0062] The obtained composite conductive particles are placed in an impregnation tank, and the obtained first slurry is slowly poured in. After impregnation for 6 minutes, the composite conductive particles are taken out and dried in a drying oven at 80° C. for 2 hours to remove excess water, and the impregnation and drying process is repeated until the desired shell thickness of 50 μm is reached to obtain a core-shell structure material;

[0063] (3) Preparation of carbon ceramic resistors:

[0064] The obtained core-shell structure material was placed in a mold and preformed at 100 MPa, the pressure was maintained for 30 seconds, the preform was taken out, placed in an isostatic press, and isostatically pressed at 105 MPa again, the pressure was maintained for 2 minutes.

[0065] Demoulding to obtain a green body;

[0066] The obtained green body was placed in the heating chamber of the sintering equipment, and the heating rate was set to 3℃ / min. It was preheated to 600℃ and kept warm for 1h to remove organic matter and moisture. Then pressure was applied and the temperature was continued to rise to 1000℃ and kept warm for 2h. To promote the initial formation of the ceramic phase, the temperature was raised again. When the temperature reached 1300℃, opposite electrodes were set on the opposite surfaces of the green body to ensure close contact with the sample. A DC power supply was connected and the current density was set to 10mA / mm 2 , the electric field strength is 6500V / cm, the voltage is applied, the constant current time is controlled to be less than 1s, and the green body is flash-burned. After the flash-burning process is completed, it is naturally cooled to room temperature to obtain a carbon ceramic resistor.

[0067] Example 2

[0068] The present embodiment provides a carbon ceramic resistor, in which, based on the mass of the composite conductive particles as 100%, the proportion of the conductive carbon is adjusted from 4% to 3%, and the proportion of aluminum oxide is adjusted from 96% to 97%; that is, in step (1) of the preparation method of the carbon ceramic resistor, the mass ratio of citric acid monohydrate to aluminum precursor aluminum sol is adjusted from 25:75 to 17:83. Except for the above, other conditions are exactly the same as those in Example 1.

[0069] Example 3

[0070] The present embodiment provides a carbon ceramic resistor, in which, based on the mass of the composite conductive particles as 100%, the proportion of the conductive carbon is adjusted from 4% to 2%, and the proportion of aluminum oxide is adjusted from 96% to 98%; that is, in step (1) of the preparation method of the carbon ceramic resistor, the mass ratio of citric acid monohydrate to aluminum precursor aluminum sol is adjusted from 25:75 to 20:80. Except for the above, other conditions are exactly the same as those in Example 1.

[0071] Example 4

[0072] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, in step (3), the isostatic pressing pressure is adjusted from 105 MPa to 100 MPa. Except for the above, other conditions are exactly the same as those in Example 1.

[0073] Example 5

[0074] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, in step (3), the isostatic pressing pressure is adjusted from 105 MPa to 115 MPa. Except for the above, other conditions are exactly the same as those in Example 1.

[0075] Example 6

[0076] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, the number of repeated immersion and drying processes in step (3) is reduced until the shell thickness reaches 35 μm. Except for the above, other conditions are exactly the same as those in Example 1.

[0077] Example 7

[0078] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, the number of repeated immersion and drying processes in step (3) is reduced until the shell thickness reaches 40 μm. Except for the above, other conditions are exactly the same as those in Example 1.

[0079] Example 8

[0080] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, the number of repeated immersion and drying processes is increased in step (3) until the shell thickness reaches 60 μm. Except for the above, other conditions are exactly the same as those in Example 1.

[0081] Example 9

[0082] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, in step (3), the time of each immersion is adjusted from 6 minutes to 4 minutes. Except for the above, other conditions are exactly the same as those in Example 1.

[0083] Example 10

[0084] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, in step (3), the time of each immersion is adjusted from 6 minutes to 5 minutes. Except for the above, other conditions are exactly the same as those in Example 1.

[0085] Embodiment 11

[0086] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, in step (3), the temperature of the reheating after preheating is adjusted from 1000°C to 850°C. Except for the above, other conditions are exactly the same as those in Example 1.

[0087] Example 12

[0088] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, in step (3), the temperature of the reheating after preheating is adjusted from 1000° C. to 900° C. Except for the above, other conditions are exactly the same as those in Example 1.

[0089] Example 13

[0090] This embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, in step (3), the temperature of the reheating after preheating is adjusted from 1000°C to 1100°C. Except for the above, other conditions are exactly the same as those in Example 1.

[0091] Embodiment 14

[0092] The present embodiment provides a carbon ceramic resistor. In the preparation method of the ceramic resistor, in step (3), the obtained green body is placed in a normal pressure sintering furnace, and the heating rates are set to 5°C / min, 4°C / min, 3°C / min, 2°C / min, and 1°C / min, respectively. According to the sintering furnace heating system, the sintering temperature of the green body is increased to 1300°C, kept warm for 2 hours, and then cooled with the furnace to obtain a carbon ceramic resistor.

[0093] Comparative Example 1

[0094] This comparative example provides a carbon ceramic resistor, and the preparation method thereof comprises:

[0095] The ceramic matrix powder, carbon black and alumina are mixed evenly in the proportion of 87%, 4% and 9% to obtain a mixed powder. The mixed powder is placed in a mold with a diameter of 20 and a green body is obtained by pressing. The green body is placed in a 105MPa isostatic press for isostatic pressing. The green body is placed in a sintering furnace and sintered at 1300°C, and then cooled with the furnace to obtain a carbon ceramic resistor.

[0096] Characterization and Testing:

[0097] The carbon ceramic resistors obtained in the examples and comparative examples were tested as follows: the volume density and water absorption were measured by weighing method according to GB / T25995-2010 standard; the compressive strength was measured by pressure test in accordance with GB / T 8489-2006 standard. The resistance value was tested using a high-precision resistance meter at room temperature and without electromagnetic interference. For the temperature coefficient test, the carbon ceramic resistor needs to be placed in a temperature control box, the resistance value is measured at different set temperatures, and the data is recorded to calculate the temperature coefficient. For the voltage coefficient test, a high-voltage power supply needs to be used to provide a stable voltage output, and the resistance value is measured at different set voltages to calculate the voltage coefficient.

[0098] The results are shown in Table 1.

[0099] Table 1

[0100]

[0101] The performance requirements of the new carbon ceramic closing resistor are evaluated according to the industry standards: volume density ≥2.25g / cm3, compressive strength ≥120MPa, resistance value 5±0.25Ω, temperature coefficient -0.05~0.1% / ℃, voltage coefficient -7.5~-0.5%·cm / kV.

[0102] It can be seen from Table 1 that, by comparison, the mechanical properties and electrical properties of the carbon ceramic resistor of Comparative Example 1 are much lower than those of the carbon ceramic resistor containing a continuous conductive interlayer prepared in Example 1.

[0103] The bulk density of Example 1 is 2.28 g / cm 3 , while the volume density of other embodiments fluctuates around this value. Changes in volume density. This may be due to slight changes in parameters such as the ratio of raw materials, molding pressure, and sintering temperature and time during the preparation process, which lead to changes in the porosity, grain size and distribution inside the material. An increase in porosity will reduce the volume density of the material, while the growth and densification of grains will increase the volume density. Changes in volume density will directly affect the mechanical and electrical properties of the material, such as hardness, toughness, and conductivity. The compressive strength of Example 1 is 157MPa, while the compressive strength in other embodiments fluctuates between 154MPa and 165MPa. Fine grains and uniform distribution can improve the strength and toughness of the material, while defects and impurities at the grain boundaries may become the source of crack initiation and expansion, reducing the compressive strength. In addition, an increase in porosity will also reduce the compressive strength of the material. The resistance value of Example 1 is 4.83Ω, while the resistance values ​​in other embodiments vary between 4.80Ω and 5.20Ω. Changes in composition affect the material's carrier concentration and mobility, which in turn affects the resistance value. Changes in microstructure, such as changes in grain size, shape, and distribution, as well as changes in grain boundary characteristics, affect the electron transport path and scattering mechanism in the material, which in turn affects the resistance value. An increase in porosity increases the scattering of electrons in the material, leading to an increase in resistance.

[0104] The bulk density of Comparative Example 1 is 2.20 g / cm 3 , and the compressive strength is 110MPa, which are lower than most of the values ​​in Example 1 and the newly added examples. This may be due to the uneven distribution of carbon black in the comparative example, resulting in a poor microstructure of the prepared material. In addition, the sintering process is accompanied by the generation of gas. Compared with ordinary sintering, oscillation sintering can make the gas overflow during the sintering process, and the green body sintered by oscillation sintering is denser, resulting in increased compressive strength. The resistance value of Comparative Example 1 is 6.00Ω, which is much higher than the values ​​in Example 1 and other examples. This may be because the carbon black is agglomerated together in the carbon composite ceramic, and the agglomeration of carbon black may lead to a decrease in carrier concentration and mobility, thereby increasing the resistance value.

[0105] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0106] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0107] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0108] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A carbon ceramic resistor, characterized in that: The invention comprises a ceramic matrix in which composite conductive particles are dispersed. The composite conductive particles include conductive carbon and aluminum oxide. The composite conductive particles have multi-level pores.

2. The carbon ceramic resistor according to claim 1, characterized in that: The composite conductive particles are spherical; Preferably, the particle size of the composite conductive particles is 80 to 120 μm; Preferably, the multi-level pores include nanopores and micropores; the pore size of the nanopores is 10 to 50 nm; the pore size of the micropores is 10 to 20 μm; Preferably, based on 100% of the mass of the composite conductive particles, the conductive carbon accounts for 2% to 7%, and the aluminum oxide accounts for 93% to 98%; Preferably, based on the mass of the carbon ceramic resistor being 100%, the composite conductive particles account for 9% to 15%, and the ceramic matrix accounts for 85% to 91%.

3. A method for preparing a carbon ceramic resistor according to claim 1 or 2, characterized in that: include: The composite conductive particles are mixed with a ceramic matrix raw material, and a first granulation is performed so that the ceramic matrix raw material covers the composite conductive particles to form a core-shell structure material; The core-shell structure material is molded to obtain a green body; and the green body is subjected to a first sintering to obtain a carbon ceramic resistor.

4. The method for preparing a carbon ceramic resistor according to claim 3, characterized in that: Taking the total mass of the ceramic matrix raw material as 100%, the ceramic matrix raw material includes 48% to 50% of bauxite, 18% to 20% of potassium feldspar, 10% to 12% of kaolin and 20% to 22% of clay.

5. The method for preparing a carbon ceramic resistor according to claim 3 or 4, characterized in that: The first granulation method includes impregnation granulation; the impregnation granulation includes preparing the ceramic matrix raw material into a first slurry, and impregnating the composite conductive particles in the first slurry, so that the ceramic matrix raw material covers the composite conductive particles to form the core-shell structure material; Preferably, the first slurry is pre-ball milled for 4 to 8 hours; Preferably, the immersion time is 5 to 10 minutes; Preferably, after the impregnation, the mixture is dried at 70 to 90° C. for 1 to 3 hours; Preferably, the dipping and drying process is repeated at least twice until the thickness of the shell layer reaches 40-60 μm; Preferably, the ceramic matrix raw material and water are prepared into the first slurry according to a solid-liquid mass ratio of 1:(0.5-2).

6. The method for preparing a carbon ceramic resistor according to any one of claims 3 to 5, characterized in that: The molding comprises pre-molding at 90-110 MPa, and then increasing the molding pressure to 95-115 MPa for isostatic pressing; Preferably, the first sintering method comprises oscillating pressure sintering assisted flash sintering; Preferably, the process of oscillating pressure sintering assisted flash sintering includes: preheating the green body to 550-650°C and keeping it warm for 1-3 hours to ensure temperature uniformity; then, starting to apply pressure and simultaneously raising the temperature to 900-1100°C, and then keeping it warm for 0.5-1 hour to promote material densification and grain growth; finally, when the temperature reaches the flash trigger temperature of 1200-1400°C, setting opposite electrode sheets on the opposite side surfaces of the green body and applying 8-12 mA / mm 2 The current density and electric field strength are 6000-7000V / cm, and the constant current time is controlled to be less than 1 second for flash burning.

7. The method for preparing a carbon ceramic resistor according to any one of claims 3 to 6, characterized in that: The method for preparing the composite conductive particles comprises: A carbon precursor and an aluminum oxide precursor are mixed in a liquid phase system to obtain a second slurry; the second slurry is subjected to a second granulation to obtain a composite precursor; and the composite precursor is subjected to a second sintering to obtain composite conductive particles with multi-level pores.

8. The method for preparing a carbon ceramic resistor according to claim 7, characterized in that: The carbon precursor includes citric acid monohydrate; Preferably, the aluminum oxide precursor includes aluminum sol; the mass concentration of the aluminum sol is 10% to 40%; Preferably, based on the total mass of the carbon precursor and the aluminum oxide precursor being 100, the carbon precursor accounts for 20% to 30%; Preferably, the viscosity of the second slurry is 1000-2000 cP; Preferably, the second granulation method comprises spray granulation; Preferably, the air inlet temperature of the spray granulation is 200-250°C, and the air outlet temperature is 100-120°C; Preferably, the second sintering temperature is 900-1100°C.

9. A closing resistor, characterized in that: The closing resistor contains the carbon ceramic resistor according to claim 1 or 2, or contains the carbon ceramic resistor obtained by the preparation method according to any one of claims 3-8.

10. A method for manufacturing a closing resistor according to claim 9, characterized in that: The manufacturing method comprises sequentially subjecting the carbon ceramic resistor to mechanical grinding and electrode coating to obtain a closing resistor.

Citation Information

Cited By

  • Core-shell structure carbon ceramic resistor material, preparation method and resistor

    CN121824097A